Balearic Islands (Eastern Algeria) (Mallorca - Menorca - Land) A study in its Islamic history and civilization (Journal of the College of Basic Education, 2022)
After God, may He be glorified and exalted, bestowed upon the Arabs the grace of Islam, when He brought them out of the darkness into the light and commanded them to strive in the way of God to bring the nations of the earth out of the darkness and ignorance in which they live, the masses of the Arab Islamic armies set out heading east and west to open the countries to Islam, so the conquest of the Iberian Peninsula was (Spain) a great event that culminated in the building of a great Islamic state that lasted for eight centuries, as it brought the Arab Islamic systems and civilization to the depths of Europe, and some orientalists still acknowledge this merit.